(3Gdadc GdOGFQ Ydi GdeKd GdSGFQs - (3CHh MGeO YR GdOjf YHO GdMejO Hf CHi GdMOjO GdeOGFfi GdeYJRdis; (3fUQ Gddg Hf eMeO GdehUdj GHf GdGKjQ GdLRQjs ((3MGLi Hf NejS Hf Sja GdOjf GdZQhi GdfLai s)
(3ChdgG (B:s
(3GdMeO ddg GdPi adhJ Hjf Ybhd GdHTQ hCNdGbge ceG aGhJ Hjf CYeGQge hCQRGbge hHYO abO hbaJ Ydi cJGH GdeYQha HGHf GdCKjQ GdLRQi GdeSei cJGH GdeKd GdSGFQ ai COH GdcGJH hGdTGYQ s
(3BNQgG (B:s
(3acGf GdETJZGd HgG hGdHMK ajgG JVjYkG ddhbJ ef Ke hQCjJ Cf CNJe GdcJGH gGgfG MGeOkG ddg heUdGjkG Ydi NjQ Ndbg eMeO GdfHi GdCei hYdi Bdg hGUMGHg s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3fbdgG GdfGSN ef fSNI fbdJ ef fSNI fbdJ ef OSJhQ GdeUfa hCUdM efgG Gdfbd s
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdCOHs